Inequality of water allocation and policy response considering virtual water trade: A case study of Lanzhou city, China. (1st October 2020) - Xu, Zhongwen; Yao, Liming; Zhang, Qiong; Dowaki, Kiyoshi; Long, Yin
Abstract: Due to the unequal distribution of water resources, challenges remain in the water resource allocation. How to upgrade water use efficiency has become an urgent issue worldwide, especially in arid and semiarid areas. Therefore, water allocation management that balancing the trade-off between economic development and environmental protection has become a hot topic in recent years but lacks applicational analysis. To narrow this knowledge gap, this study introduces a food-water nexus to the case study by introducing virtual water trade into the proposed model. Given climate change's impacts on seasonal water supply, this study divides a planning year by season. Under this framework, a bi-objective dynamic model for water allocation is formulated and applied to a typical water-arid area, Lanzhou, China in 2017. The study aims to produce an optimal water resource allocation strategy among industrial, domestic, agricultural and ecological sectors and reveal the effects of variable precipitation on the water allocation strategy. Finally, this model is found to reach an economic-environmental balance based on the Pareto frontier depicted by the solved solutions. The results show that the gap between supply and demand will be supplemented by virtual water, and virtual water trade has simultaneously increased economic benefit, saved water and improved integrated water-use efficiency. In addition, distinct strategies about water allocation and virtual water trade are identified in spring, summer, autumn and winter. The study also finds that virtual water trade contributes to equity improvement of water resource allocation, which can provide vital information on common prosperity for future water resource management at the regional level. Highlights: A bi-objective dynamic model to optimize seasonal water allocation and VWT pattern. 1.51∗10 7  m 3 of irrigation water is saved via incorporating VWT in the planning year. Water allocation inequity is redressed by optimizing water allocation and VWT together. Considering economic-environment sustainability for optimizing water-food nexus pattern.